Properties of Folate Binding Protein Purified from Cow’s Milk - . SUBANDRATE; DWIRINI RETNO GUNARTI; MOHAMAD SADIKIN (HAYATI Journal of Biosciences, 2012)
Folic acid played an important role in the metabolism of the body. To measure the serum folic acid levels could use the folate binding protein (FBP) from cow’s milk with a technique analogous to ELISA.  The aims of this study were to identify characteristics of FBP from cow’s milk and binding capacity of FBP to folic acid and to purify FBP from other whey protein passed through DEAE-cellulose chromatography column. Each of DEAE-cellulose peaks was passed in affinity chromatography column. FBP was released from affinity column with sodium acetate buffer pH 3.5. The purity of obtained FBP was demonstrated by a single spot in SDS-PAGE analysis and the estimated molecular weight of FBP was around 31 kDa. Our study indicated that 1 mol FBP bound 1 mol folic acid. Alkylation with iodoacetic acid decreased the binding capacity of FBP which suggested the presence of a–SH or imidazol group in its active site. The importance of disulfide bridge was proven by decreasing of folate binding capacity of FBP after b-mercaptoethanol treatment. In contrary, the folate binding didn need Ca2+ ion, as indicated by EDTA test which gave the same result as control.